Pengaruh Work-Family Conflict terhadap Kesejahteraan Psikologis pada Ibu Bekerja dengan Dukungan Sosial sebagai Moderator - Muhammad Azruddin Nasution; Zulkarnain Zulkarnain; Ari Widiyanta (Jurnal Ragam Pengabdian, 2026)
Working mothers often face competing demands from work and family roles, which can trigger work-family conflict and affect psychological well-being. This study examined the effect of work-family conflict on psychological well-being among working mothers and tested social support as a moderator. Using a quantitative correlational design, data were collected from 385 married, employed mothers with children, selected through purposive sampling. Measurements included the Psychological Well-Being Short Scale, the Work-Family Conflict Scale, and the Social Provision Scale. Data were analyzed using simple linear regression and moderated regression analysis (MRA). Results showed that work-family conflict had a significant negative effect on psychological well-being (B = -0.759, β = -0.446, t = -9.756, p < .001, R² = .199), indicating that higher work-family conflict was associated with lower psychological well-being. However, the interaction between work-family conflict and social support was not significant (B = -0.007, β = -0.049, t = -1.079, p = .281), showing that social support did not moderate this relationship. These findings suggest that psychological well-being among working mothers is closely tied to the dynamics of work-family conflict. Although social support remains relevant to well-being, it did not alter the strength of this relationship.